The Impact of the Test Length On the Accuracy of Estimates of the Ability Indicators for Individuals and The Information Function of the Test - Geoffrey Anthony Bao Condor; Teodoro Edgardo (Al-Qanṭara, 2022)
Abstract This study aimed at verifying the impact of the test length on the accuracy of estimates of the ability indicators for individuals and the information function of the test according to the item response theory, to achieve the objective of the study, a multiple-choice test in chemistry was constructed for students of the 10th grade in Jordan. The test is made up of three models of the same content, but vary in the number of items, the extended test, the intermediate test, and the short test. The(Bilog-Mg) program was used to analyze the 915 students' responses for all three test models according to the two-parameter logistic model. The study results revealed no statistically significant differences between the means of the standard error for estimating individual ability indicators attributed to the length of the test. The results of the study showed that the information function of the test differed with the variation of the test models, as well as the absence of statistically significant differences attributed to the values of the empirical validity coefficients.